Diagnóstico da supressão de vegetação nativa para o processo de urbanização em áreas rurais às margens de lagos artificiais com uso de geotecnologias - Souza, Letícia Lemos de (2023)
Rural lands can be urbanized by regulations aimed at the economic development of a region and, consequently, clandestine, by promoting urban dispersion towards areas that should be preserved. Contrary to the environmental issue, Federal Law (LF, in Portuguese abbreviation) no. 13,465 (Brazil, 2017) started to allow the regularization of consolidated informal urban centers independent of their location, which benefited both occupations by low-income populations located in special zones of social interest (REURB-S), and others undertaken by groups with various interests (REURB-E), such as the majority of clandestine subdivisions around the Miranda Reservoir, one of the artificial reservoirs formed with the implementation of Hydroelectric Power Plants (UHEs) on Araguari River in Uberlândia, Minas Gerais, benefiting not only from the aforementioned LF, but also due to the creation, in 2019, of municipal regulations that transformed rural area into a Specific Urbanization Zone (ZUE). To understand the environmental impacts caused by the principle of this urbanization, it would be necessary to diagnose what native vegetation was removed due to the land subdivision. In fact, surveying soil use and coverage using traditional techniques would be time-consuming and costly, given the size of the area; however, satellite images and digital processing techniques (PDI) have been widely used, especially because they cover large areas at a lower cost in the survey stage. Among the PDI techniques, the Normalized Difference Built-up Index (NDBI) and the Normalized Difference Vegetation Index (NDVI) stand out for their variety of applications in use and coverage studies. land, whose interests refer, respectively, to the built or vegetated area. In view of this, the evolution of the suppression of native vegetation was mapped through the NDVI and the increase in area built by the NDBI, by recording the advance of anthropization in ZUE 5, which confirmed the loss of areas of vegetative vigor (natural, agricultural or pastures) and the increase in land division (regular or irregular) for housing purposes. Urbanization due to urban development vectors causes the loss of biodiversity, the sealing of the soil, the generation and transport of solid waste to the dam, among others. The diagnosis now carried out supports the definition of guidelines that mitigate urban and environmental impacts and lead to environmental preservation and urban ecology.